The relationship between obesity associated weight-adjusted waist index and the prevalence of hypertension in US adults aged ≥60 years: a brief report - Wang, Jiao; Yang, Qing-Ye; Chai, Dong-jian; Su, Yue; Jin, Qi-Zhi; Wang, Jin-Hua (Frontiers in Public Health, 2023)
Objectives The main objective was to examine the relationship between weight-adjusted waist index (WWI) and the prevalence of hypertension among individuals aged ≥60 years who participated in the NHANES between 2011 and 2018 years. Methods The data for this study were obtained from the National Health and Nutrition Examination Survey (NHANES) 2011–2018. In this population-based study, we focused on participants who were over 60 years old. Data were collected from the aforementioned survey, and the variable of interest was WWI, which was calculated as waist (cm) divided by the square root of body weight (kg). Multivariable logistic regression model was applied to calculate adjusted ORs with 95% CIs in order to explore any possible correlation between WWI and the prevalence of hypertension. Subgroup analysis were used to verify the stability of the relationship between WWI and the prevalence of hypertension. The interaction tests were also conducted in this research. Results Results revealed that adults aged ≥60 years who were in the highest WWI quartile had significantly higher chances of developing hypertension when compared to those in the lowest quartile, after adjusting for covariates and potential confounders (p < 0.001). Conclusion These findings suggest that there is a strong correlation between elevated levels of WWI and the risk of developing hypertension among older adults. As such, WWI could serve as a unique and valuable biomarker for identifying hypertension risk at an earlier stage in the older adults population.